Performance and Accuracy Enhancement of Cloud Environment During Precision Agriculture - Ram Lakhan; Er. Krishan Kumar (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
In precision agriculture, the data acquired by sensors are classified into groups according to a variety of parameters, including the existence of animals, the degree to which soil nutrition is present, and the quantity of soil moisture. In the event that any unfavorable conditions take place, a signal of warning will be sent. On the other side, if the conditions are right, the surgical procedure won’t be done at all. Several recently concluded research projects related to intelligent solutions for healthcare and agricultural problems have made use of a variety of techniques from the disciplines of cloud computing, IoT, and wearable robots. These methodologies were used in the study. Enhancing the performance and accuracy of cloud environments for use in precision agriculture is the primary emphasis of the research being done at the moment. The problem-solving aspects of the area have often been the focal point of the study that has been carried out in relation to this issue. Despite this, there are still many obstacles to overcome with regard to the implications of cloud computing and agricultural precision. One of these challenges is the necessity of including an accuracy mechanism in order to ensure the integrity of Agriculture precision while it is operating in an environment that includes Cloud Computing. This is a necessity because one of these challenges is the necessity of including an accuracy mechanism. In addition to this, the traditional approaches to research need to be enhanced in order to deliver a greater degree of accuracy.